VALUE ORIENTATIONS AND BEHAVIORAL STRATEGIES OF MILITARY PERSONNEL IN WAR CONDITIONS - Olefirenko, Yuliia; Proskurka, Nataliia (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2024)
The article presents the results of a study of the relationship between military personnel's value orientations and their coping strategies. The purpose of the study is to theoretically analyze and experimentally investigate the peculiarities of military behavior in war and the influence of value orientations on the choice of their coping strategies. The following methods were used in the study: theoretical (literature analysis, classification, systematization, generalization of the results), empirical (survey, testing) and methods of statistical and mathematical data processing (SPSS 19.0). Psychodiagnostic techniques were used in the empirical study: "Value Orientations" by M. Rokic, "Ways of Coping Behavior" by R. Lazarus. Results. In the course of the experimental study, it was found that for servicemen, the significant terminal values are "happy family life", "love", "health", "active life" and "good, loyal friends". These values help servicemen to fulfill their tasks. At the same time, the instrumental leading values of "accuracy", "honesty", "good manners", "strong will" and "self-control" help servicemen adapt to the conditions of combat operations. The results of the study of coping behaviors revealed that the most adaptive coping for most servicemen is acceptance of responsibility (59.2%). The most maladaptive is self-control (37.0%). The results of the correlation analysis revealed connections between the coping strategies "self-control", "acceptance of responsibility", "avoidance" and instrumental values "high demands", "intransigence to shortcomings" and "tolerance". And also, between the coping strategies "confrontation", "distancing", "planned problem solving", "positive reassessment" and terminal values: "active life", "productive life", "freedom", "social vocation". Conclusions. The results of the study have shown that the value orientations of military personnel are related to the choice of adaptive and constructive coping strategies and affect the psychological state of the military and their overall combat readiness